Microstructure and texture evolution of 2A12 aluminum alloy semi-solid billet prepared by SIMA process - Ming Chang; Boyang Liu; ShuQin Fan; YongFei Wang; ShuangJiang Li; Kun Li; Shengdun Zhao (Journal of Materials Research and Technology)
In order to make up for the lack of research on the preparation process of semi-solid billet of 2A12 aluminum alloy, this paper adopts strain-induced melting activation (SIMA) process to prepare semi-solid billet of 2A12 aluminum alloy, and studies the effect of different SIMA process parameters on the microstructure and texture evolution. The results indicated a notable increase in both the average grain size (AGS) and shape factor (SF) with prolonged isothermal time under the condition of constant isothermal temperature. When the isothermal time is the same, the AGS is larger at low isothermal temperature, the SF is higher at high isothermal temperature, and the grain spheroidization is more obvious; The influence of the uneven strain distribution of the compression sample on the microstructure evolution during the subsequent semi-solid isothermal treatment (SSIT) process was studied by finite element method; At an isothermal temperature of 590 °C and an isothermal time of 15 min, the recrystallization is basically completed, and the elongated grains are completely transformed into spherical isaemic crystals. The main texture types of the original extruded sample and the compression sample are <110> ‖CD and <010> ‖CD texture, respectively. The SSIT process will make the grain orientation approach to random orientation; The strong segregation of Cu and mild segregation of Mg and Zn were observed at the grain boundary during SSIT process; A suitable coarsening kinetic equation was determined, and the influence of isothermal temperature on the coarsening rate constant was studied.